Effects of Local Indigenous Games on Cognitive Function, Physical Literacy and Academic Achievement Among Children 8 to 12 Years Old - Mohammad Hossein Manzari Tavakoli; Masoumeh Shojaei; Kivan Norouzi (University of Tehran, 2021)
The aim of this study was to investigate the effect of local indigenous games on cognitive function, physical literacy, and academic achievement of children 8 to 12 years old. The participants were 60 male elementary school students with an average age of 10.32. The research was conducted in four phases, include Pre-test,, Training phase in local indigenous games and dynamic courtyard,, Posttest, and Follow-up. The local indigenous games training consisted of twelve traditional-indigenous games that relied highly on physical activity and interpersonal interactions skills. In addition, the control group performed dynamic courtyard training that included some predetermined activity in school. The descriptive statistics and statistical procedures of Mixed ANOVA 2*3 and Bonferroni post-hoc were utilized to analyze data. Results were indicated that the amount of cognitive function for the local indigenous games group was higher than the control group. In addition, the physical literacy of the local indigenous games group was increased more than the control group. Moreover, academic achievement points for the local indigenous games group and the control group in the pre-test to post-test were enhanced, but this increase was higher in the local indigenous games group. The results of this study, were suggested that local indigenous games as a better model compared to the dynamic courtyard model for improving cognitive function, physical literacy, and academic achievement among children 8 to 12 years old.